Research efficiency in manufacturing: an application of DEA at the industry level - Jens Schmidt-Ehmcke; Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper analyzes research efficiency at the industry level in manufacturing for 13 European member and four nonmember countries during 2000 and 2004. A unique dataset was compiled that matches patent applications at the European Patent Office (EPO) to industry-specific R&D inputs from EU KLEMS. We find that Germany, the United States, and Denmark have the highest efficiency scores on average in total manufacturing. The main industries that are at the technology frontier are those involved in electrical and optical equipment and machinery. Separate frontier estimations for these industries, conducted without the constraint of a constant technology frontier, provide additional support for our results.
Keywords: C14; L60; O31; O57; 330; R&D efficiency; industry level; data envelopment analysis; manufacturing; Industrielle Forschung; Patent; Technische Effizienz; Data-Envelopment-Analyse; Deutschland; USA; Dänemark